A simple, wide bandwidth, biopotential amplifier to record pacemaker pulse waveform - Bifulco P (Dove Medical Press, 2016)
Paolo Bifulco,1 Gaetano Dario Gargiulo,2 Maria Romano,3 Mario Cesarelli1 1Department of Electrical Engineering and Information Technology, University of Naples “Federico II”, Naples, Italy; 2The MARCS Institute, Western Sydney University, Penrith, NSW, Australia; 3DMSC, University “Magna Graecia”, Germaneto, Catanzaro, Italy Abstract: Reliable detection of pacemaker pulses is getting more and more important in electrocardiography (ECG) diagnosis. Many studies recommend ECG amplifiers with higher bandwidth to prevent errors. In the past, few pilot studies showed that analysis of pacemaker pulses waveform can enhance diagnosis (eg, lead failure and fractured wire), but they were carried out with inadequate instrumentations for clinical practice. Typically, pacemaker pulses last hundreds of microseconds, edges of pulses elapse in few microseconds, and amplitude may exhibit large variations from few millivolts to volts. Pulse waveforms change often and depend on pacemaker type and programming. A simple, biopotential amplifier made of a few off-the-shelf components is proposed. The circuit fulfills specifications for biopotential amplifiers and offers a large bandwidth (~1 MHz). Therefore, it is able to accurately record time course of pacemaker pulses and allows highly accurate pulse detection and timing. Signals can be easily displayed and acquired by means of a standard, battery-powered oscilloscope. Pacemaker pulse vectorcardiography can be obtained by using two or more, wideband channels. Some exemplificative waveforms recorded during patient’s periodic medical examination are reported. The proposed circuit offers simultaneous conventional ECG signal as an additional output. Keywords: wideband biopotential amplifiers, pacemaker pulse waveform, electrocardiography device